Thermally stable cobalt amide cyanide as high-activity and durable bifunctional electrocatalyst toward O2 and CO2 reduction. (1st September 2020) - Li, Yaping; Ci, Suqin; Cai, Pingwei; Senthilkumar, N.; Wen, Zhenhai
Abstract: The electrocatalytic oxygen reduction reaction (ORR) and carbon dioxide reduction reaction (CO2 RR) are considered as major strides for the development of a global-scale sustainable energy system, owing to their potential in neutralizing carbon emissions, generating value-added product, and delivering clean energy. However, the practicability of ORR and CO2 RR is hampered by the sluggish kinetics and instability of the catalyst materials, calling for thirst for exploring efficient and stable electrocatalyst. With this concern, we herein report a hybrid (c-CoACC/CNTs) with carbon nanotubes (CNTs) decorating cubic cobalt amide cyanide complex (c-CoACC), which is synthesized by using molten salt (MS) assisted method and exhibits highly crystalline and thermally stable features. The c-CoACC/CNTs exhibit profound ORR activity with the onset and half-wave potential (E1/2 ) of 0.972 and 0.87 V in alkaline conditions, respectively. The practical application of c-CoACC/CNTs as ORR catalysts has been verified in a home-made zinc-air battery, which is capable of releasing a maximum power density of 188 mW cm −2 in comparison with 175 mW cm −2 in the Pt/C based zinc-air battery. Furthermore, the c-CoACC/CNTs exhibits desirable electrocatalytic properties toward CO2 -to-CO conversion in 0.5 M KHCO3 with a tunable production ratio between CO and H2, yielding a maximum Faraday efficiency of 83.8% at −0.78 V vs. RHE. The attractive electrocatalytic properties in the c-CoACC/CNTs can be attributed to the improved electroactive sites relative to individual c-CoACC and CNT, reduced diffusion resistance, and enhanced three-phase boundaries. Notably, the c-CoACC/CNTs perform encouraging stability in the catalysis of ORR and CO2 RR under various electrochemical regimes and conditions, directing a viable path for a future global-scale sustainable energy system.